The Process Approach and UAE High School Students' Attitudes Towards Writing - Aouina, Hichem Taieb (2006)
A Master of Arts Thesis in Teaching English to Speakers of Other Languages (TESOL) by Hichem Taieb Aouina Entitled, "The Process Approach and UAE High School Students' Attitudes Towards Writing," August 2006. Thesis Advisor is Dr. Rodney Tyson. Available are both Soft and Hard Copies of the Thesis.